The Role of Technology in Non-Formal Education in Rural South Africa - Teboho Maseko; Lesedi Mokoena; Dineo Mabuza; Josefa Flores; Andres Villanueva (Yayasan Adra Karima Hubbi, 2025)
Background. Non-formal education plays a significant role in rural South Africa, where formal education systems often face challenges such as limited infrastructure and financial resources. The integration of technology can help bridge these gaps, offering innovative ways to deliver education in under-resourced areas. Purpose. This study aims to explore the role of technology in enhancing non-formal education in rural South Africa, particularly focusing on its effectiveness in improving access, quality, and engagement for learners. Method. A qualitative research approach was employed, with interviews and focus group discussions conducted among educators, students, and community members in rural areas. Results. The findings reveal that technology, particularly mobile learning platforms and digital resources, has significantly enhanced accessibility to educational materials. Additionally, it has contributed to more interactive and engaging learning experiences, though challenges such as unreliable internet connectivity and limited technological skills among educators persist. Conclusion. The study concludes that while technology has great potential to improve non-formal education in rural South Africa, efforts must be made to address the challenges of infrastructure and digital literacy.